Reef Check Data Reveal Rapid Recovery From Coral Bleaching In The Mamanucas, Fiji - Harding, Simon P.; Solandt, Jean-Luc; Walker, Ryan C.J.; Walker, Dianne; Taylor, Jessica; Haycock, Simon; Davis, Melanie T.; Raines, Peter (Silliman Journal, 2022)
Twenty two fringing reef sites within the Mamanuca 1. Islands, western Fiji were surveyed during 2001 and 2002, using Reef Check methods. A mean increase of 14.3% in hard coral cover was recorded over the 12-month period. This increase in hard coral cover suggests a significant recovery of scleractinian coral colonies that were originally impacted by the 2000 mass bleaching episode in the South Pacific. The event was reported to have caused >80% coral mortality in the southern and eastern regions of Fiji. Between 2001 and 2002 the coral reefs of the Mamanucas progressed from "poor" to "fair" in accord4nce with the Association of South East Asian Nations (ASEAN) system for describing the health of coral reefs. Our results also show that trained non-specialist volunteers undertaking marine surveys such as Reef Check can competently collect simple, yet important quantitative data regarding the physical health of coral reefs.